2005
DOI: 10.4049/jimmunol.175.6.3769
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a Dromedary Heavy Chain-Only Antibody and B Cell Development in the Mouse

Abstract: Material

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 61 publications
1
19
1
Order By: Relevance
“…Moreover, we see no LC rearrangement and conclude that LC are not required for further B cell differentiation. The difference in our results and those of Zou et al (13) may be explained by the level of expression of the locus (and, thus, signaling) because of the LCR on our constructs. Our results confirm that truncated HCAb lacking CH1 (24) or VH and CH1 (36) cannot associate with SLCs and fail to activate gene rearrangement.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Moreover, we see no LC rearrangement and conclude that LC are not required for further B cell differentiation. The difference in our results and those of Zou et al (13) may be explained by the level of expression of the locus (and, thus, signaling) because of the LCR on our constructs. Our results confirm that truncated HCAb lacking CH1 (24) or VH and CH1 (36) cannot associate with SLCs and fail to activate gene rearrangement.…”
Section: Discussioncontrasting
confidence: 56%
“…IgG1 expression from the pro-B cell stage onwards, was shown to substitute for IgM in Rag2 Ϫ/Ϫ B cell development (35). Recently, it also was shown that a prerearranged camelid IgG2a partially rescues B cell development in one transgenic line in a MT (and a C⌬ Ϫ/Ϫ ) background (13). In our case, IgM or IgG lacking CH1 rescue B cell development in 10 of 10 independent lines.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Previous studies using mice transgenic for chimeric dromedary or llama/human IgH loci reported that homodimeric IgG2 can be expressed at the cell surface of developing and mature B cells and can replace IgM in its function during B cell development and as an Ag sensor (33,34). These data could be interpreted as evidence that camelid B cells expressing homodimeric IgGs develop without passing through an IgM ϩ stage.…”
Section: Membrane Igg2 Igg1 and Igm Expressed By Peripheral Blood Bmentioning
confidence: 65%
“…Bacterial species enable highyield expression of sdAb fragments in the cytosol or in periplasm, whereas yeast cells utilize secretory pathways resulting in efficient disulfide bond formation, N-glycosylation and secretion of the recombinant product into the growth medium. Recent papers also describe several alternative strategies for sdAb fragment engineering and production, such as yeast or ribosome display systems (Yau et al 2003;Ryckaert et al 2010), expression of recombinant fragments in filamentous fungi (Joosten et al 2005), in mammalian cells (Bazl et al 2007) and in transgenic mice (Zou et al 2005). Mutagenesis and recombination of CDR regions to improve the affinity and specificity of sdAb fragments have also been discussed Fanning and Horn 2011).…”
Section: Production Of Sdab Fragments Using Recombinant Technologymentioning
confidence: 99%